IMPLEMENTATION OF THE E-MONITORING AND EVALUATION POLICY OF REGIONAL APPARATUS WORK PLAN AT THE CITY OF KOTAMOBAGU CITY INVESTMENT AND ONE-DOOR INTEGRATED SERVICES DEPARTMENT - Helfrits J. Lahimade; Devie S. R. Siwij; Steven V. Tarore (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This study aims to analyze the implementation of the e-Monev policy for the Regional Device Work Plan at the Kotamobagu City Investment and One-Stop Integrated Services Office and identify its determinants. The study employed a qualitative approach, with data collection techniques including interviews, observation, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The research results indicate that the implementation of e-Monev has not been optimal. Despite being supported by regulations and technical guidelines, obstacles remain, such as data input errors, delays in input and reporting, and inconsistencies in supporting data. Determining factors affecting implementation include limited human resources, lack of commitment from implementers, and inadequate infrastructure. In conclusion, the success of e-Monev implementation is heavily influenced by communication, resources, the disposition of implementers, and bureaucratic structure. Therefore, increasing human resource capacity, strengthening commitment, and optimizing systems and infrastructure are necessary to support effective monitoring and evaluation of regional development.